Peningkatan Strategi dan Manajemen Dakwah dalam Mempertahankan Aswaja pada Rohis Sekolah - Siti Nurmahyati; Nurul Khotimah; Turhamun Turhamun; Hendri Purbo Waseso (Universitas Muhammadiyah Malang, 2026)
Purpose –Improving da'wah strategies and management is essential to maintaining the Islamic values ​​of Ahlussunnah wal Jama'ah (Aswaja) amidst the challenges of globalization and the dynamics of the digital era. This community service research aims to strengthen the understanding of the Islamic Spiritual (Rohis) administrators of schools regarding the principles of Aswaja, develop innovative da'wah strategies, and improve organizational management to support the sustainability of da'wah activities Design/methodology/approach – The community service was carried out at SMK Tujuh Lima 1 and SMK Tujuh Lima 2 Purwokerto, using the Asset-Based Community Development (ABCD) method through interviews, focus group discussions (FGDs), and training. Findings –The FGD results showed a weak understanding of Aswaja among students, a lack of skills in utilizing digital media, and organizational management challenges in carrying out da'wah. The implementation of the Aswaja strengthening workshop provided an in-depth understanding of the principles of tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and i'tidal (justice). Organizational training helped Rohis administrators increase their capacity in managing the organization effectively, including planning impactful and sustainable work programs. Information technology utilization training equips Rohis administrators with digital content production skills, such as posters and preaching videos, as well as strategies for using social media to reach a wider audience Originality/value – The community service program is effective in strengthening the understanding, strategies, and da'wah skills of Rohis administrators, so that they are able to become agents of change that are moderate, inclusive, and relevant to the challenges of the digital era.